The Foreign Policy of Cultural Heritage: A Constructivist Analysis of Cambodia’s Artefact Repatriation Efforts - Havez Al Assad; Muhammad Adel Aditya Abdullah (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Cambodia’s recent wave of cultural-heritage returns has elevated artefact repatriation from a technical heritage issue to a visible arena of international politics. This article examines why repatriation has become a sustained foreign policy priority for Cambodia and how it has been pursued in practice. The study aims to (1) map the main mechanisms of Cambodia’s repatriation strategy, (2) explain how repatriation is framed as part of post-conflict national identity, and (3) assess its broader significance for cultural sovereignty and development narratives. Methodologically, the article applies a holistic constructivist framework and uses qualitative document-based research combined with process tracing. It draws on scholarly literature, official releases, legal-diplomatic materials, and reputable investigative reporting to reconstruct the interactional pathways through which norms and identity shape policy choices. The findings show that Cambodia’s repatriation agenda is driven less by immediate material gain than by immaterial structures (historical justice, legitimacy, and identity) anchored in a “culture of restoration” centered on Angkor. Cambodia has operationalized this agenda through a hybrid toolkit: mobilizing UNESCO’s 1970 Convention, leveraging bilateral agreements, engaging in legal diplomacy, and cooperating with enforcement and museum actors. These dynamics illustrate norm diffusion and localization, where global frameworks are adapted to reinforce domestic meanings of recovery. The article concludes that Cambodia’s repatriation campaign functions as heritage diplomacy and soft power, offering practical lessons for Global South states and policy implications for museums, provenance governance, and ethical restitution frameworks.